Meprin β cleaves TREM2 and controls its phagocytic activity on macrophages. Issue 5 (1st April 2020) - Berner, Dennis Kristopher; Wessolowski, Luisa; Armbrust, Fred; Schneppenheim, Janna; Schlepckow, Kai; Koudelka, Tomas; Scharfenberg, Franka; Lucius, Ralph; Tholey, Andreas; Kleinberger, Gernot; Haass, Christian; Arnold, Philipp; et al.
Abstract: The triggering receptor expressed on myeloid cells 2 (TREM2) is a multifunctional surface protein that affects survival, migration, and phagocytic capacity of myeloid cells. Soluble TREM2 levels were found to be increased in early stages of sporadic and familial Alzheimer's disease (AD) probably reflecting a defensive microglial response to some initial brain damage. The disintegrin and metalloproteases (ADAM) 10 and 17 were identified as TREM2 sheddases. We demonstrate that meprin β is a direct TREM2 cleaving enzyme using ADAM10/17 deficient HEK293 cells. LC‐MS/MS analysis of recombinant TREM2 incubated with meprin β revealed predominant cleavage between Arg136 and Asp137, distant to the site identified for ADAM10/17. We further demonstrate that the metalloprotease meprin β cleaves TREM2 on macrophages concomitant with decreased levels of soluble TREM2 in the serum of Mep1b −/− mice compared to WT controls. Isolated BMDMs from Mep1b −/− mice showed significantly increased full‐length TREM2 levels and enhanced phagocytosis efficiency compared to WT cells. The diminished constitutive shedding of TREM2 on meprin β deficient macrophages could be rescued by ADAM stimulation through LPS treatment. Our data provide evidence that meprin β is a TREM2 sheddase on macrophages and suggest that multiple proteases may be involved in the generation of soluble TREM2.